The spectrum of bleeding in women and girls with haemophilia B. Issue 2 (27th November 2017) - Staber, J.; Croteau, S. E.; Davis, J.; Grabowski, E. F.; Kouides, P.; Sidonio, R. F.
Abstract : Although hemophilia B affects 1 in 25, 000 males there may be 3 female hemophilia B carriers per affected male. This clinical review highlights the unique challenges faced by hemophilia B carriers including the under‐recognition of bleeding symptoms associated with and without FIX deficiency, discrepancies in correlation between genotype and bleeding phenotype and therapeutic considerations utilizing clinical vignettes of common scenarios.